Implementasi Media dan Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam di Era Digital - Ega Najwa Ismail; Tia Amelda Febriani; Tiara Khaerani Hasibuan; Yandi Maulana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Islamic Religious Education (PAI) is now taught via educational media and artificial intelligence (AI) thanks to the advancement of digital technologies. This study aims to investigate the use of media and AI in PAI education, as well as its advantages, difficulties, and methods for adhering to Islamic educational principles. The study collected data from several pertinent books, journals, and scientific papers using a qualitative methodology and a library research method. The study's findings demonstrate how using digital media and artificial intelligence (AI) can make learning more dynamic, interesting, and productive while also assisting educators in creating resources and assessing student progress. However, there are a number of obstacles to the application of AI, including poor student digital and religious literacy, restricted access to technology, and reliance on technology. Therefore, the use of media and AI in PAI education should be done carefully, with instructors continuing to be the major mentors in helping students develop their Islamic beliefs and personalities